Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T17:09:10+01:00
A) (x+3)²=x²+6x+9
b) (a-2)²=a²-4x+4
c) (2x+5)²=4x²+20x+25

a) (x+2)(y+1)=xy+x+2y+2
b) (2a+1)(3-b)=6a-2ab+3-b
c) (a-1)(a²-b²)=a³-ab²-a²+b²
d) (2x-1)(y-3)=2xy-6x-y+3
e) (x-y)(a-b+9)=ax-bx+9x-ay+by-9y
f) (k²-2k+2)(t+8)=k²t+8k²-2kt-16k+2t+16
2010-01-04T17:09:27+01:00
Zad 1
(x+3)(x+3)
(a-2)(a-2)
c) (2x+5)(2x+5)
zad 2
xy+x+2y+2
b)6a-2ab+3-b
a³-ab²-a²+b²
2010-01-04T19:00:39+01:00
Zad.1
a)x²+9
b)a²+4
c)4x²+25

zad.2
a)xy+x+2y+2
b)6a-2ab+3-b
c)a<do szescianu>-ab²-a²+b²
d)2x-6x-y+3y
e)ax-bx+9-ay+by-9y
f)k²t+8k²-2kt-16k+2t+16